Boletim Offical do Governo Da Provincia De Macau E Timor (Typografia Mereantil, 1892)
Stamp of St. Joseph Seminary
Keywords: 18.Bookworm; 2.Damage

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1892)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Exposition du Dogme Catholique (P. Lethielleux, Libraire-Editeur, 1892)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Regras das Filhas da Caridade Denominadas Canossianas (Typ. Seminario De S. Jose, 1892)
Keywords: 1.Conservation 保護; 2.Damage

Resposta Ao Libro De Manoel Borges Grainha (Typ. Reis Leitao, 1892)
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair

Sancti Gregorii Magni (Libraria Academica Wagneriana, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Petite Anthologie Ou Recueil de Fables, Descriptions, Epigrammes, Pensees - A. F. Maunoury (Librairie ch. Poussielgue, 1892)
Keywords: 10.Cover Damage; 2.Damage; 22.stamp; Condition: Fair; Hard Cover; Literature

Petite Anthologie Ou Recueil de Fables, Descriptions, Epigrammes, Pensees - A. F. Maunoury (Librairie ch. Poussielgue, 1892)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

Santa Catalina de Sena - Alvarez, P. Paulino (Tipografia de El Santisimo Rosario, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Elementos de Algebra - Augusto Jose Da Cunha (Livraria de Antonio Maria Pereira, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Teaching

Vida del Angelico Protector de La Juventud San Luis Gonzaga - Cervos, P. Federico (Imprenta y Litografia de Los Huerafnos, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Sermones de Mision, Escritos unos y escogidos otros - Clret, Antonio Maria (Libreria Religiosa, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Sermones de Mision, Escritos unos y escogidos otros - Clret, Antonio Maria (Libreria Religiosa, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Sermones de Mision, Escritos unos y escogidos otros - Clret, Antonio Maria (Libreria Religiosa, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Commentarius in S. Pauli Apostoli, Epistolas - Cornely, Rudolpho (sumptibus p. lethieleux, editoris, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Bibliotheca, Canonica Iuridica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Milagros y Novena de La Santisima Virgen del Rosario - Gainza, Francisco (Imprenta Del Colegio de Sto, Tomas, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Vie des Saints - Guerin, Paul (Victor Palme, Libraire-editeur, 1892)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Vie des Saints - Guerin, Paul (Victor Palme, Libraire-editeur, 1892)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Vie des Saints - Guerin, Paul (Victor Palme, Libraire-editeur, 1892)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Cursus Scripturae Sacrae, Commentarius in Quatuor S. Evangelia - Hummelauer, Francisco de (Sumptibus P. Lethielleux, Editoris, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Vida de S. Luiz Gonzaga - J. M. Tavani D. C. D. (Administracao do Novo Mensageiro do Coracao de Jesus, 1892)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Vida de S. Luiz Gonzaga - J. M. Tavani D. C. D. (Administracao do Novo Mensageiro do Coracao de Jesus, 1892)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Moise et Darwin: l'homme de la Genèse comparé à l'homme-singe, ou, L'enseignement religieux opposé à l'enseignement athée - James, Constantin (Desclée, De Brouwer & Cie : Société de Saint-Augustin, 1892)
Keywords: 18.Bookworm; 2.Damage; Bible and evolution; Bible et évolution; Condition: Fair; Creationism; Créationnisme; Evolution (Biology) Religious aspects Christianity; Hard Cover; Religion; creationism (religious ideology)

Rubricarum: Breviarii, missalis et ritualis Romani - Joanne Josepho Dieusoitbeni (Typis Societatis Missionum Ad Exteros, 1892)
Stemp of seminario diocesano de macau
Keywords: Good

Sermao - Jose, D. Francisco (Typ. Minderva da Livaria Religiosa, 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

ceuvres oratoires de bossuet - l'abbé J. Lebarq (Desclée de Brouwer, 1892)
Stamp of bibliotheque de nazareth
Keywords: 10.Cover Damage; 18.Bookworm; Poor

ceuvres oratoires de bossuet - l'abbé J. Lebarq (Desclée de Brouwer, 1892)
Stamp of bibliotheque de nazareth
Keywords: 10.Cover Damage; 18.Bookworm; Poor

Homere Iliade, Chant Premier - M. L'abbe E. Ragon (Librairie ch. Poussielgue, 1892)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Literature

Apontamentos de Historia Universal: em harmonia com o ultimo programma official - Mattoso, José Alves (Livraria Portugueza E Estrangeira, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; History

Petite Anthologie - Maunoury, A. F. (Libraire Ch. Poussielgue, 1892)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Harmonia entre a sciencia e a fé: versão Portugueza sobre a segunda edição Hespanhola por Antonio Correia de Menezes - Mir, Miguel (J.J.R. Leitão, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Religion

Tretas D'um Senhor Professor De Lettras - P. Francisco Correa de Portocarreiro (Antonio Dourado, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair

Tretas D'um Senhor Professor De Lettras - P. Francisco Correa de Portocarreiro (Antonio Dourado, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Fair

Institutiones Philosophicae Quas Romae In Pontificia Universitate Gregoriana - P. Joanne Josephus Urraburu (Typis Viduæ ac Filiorum a Cuesta, 1892)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover; Philosophy

O Pilatinhos Conto - P. Luiz Coloma (Administracao do Novo Mensageiro do Coracao de Jesus, 1892)
Keywords: 18.Bookworm (Only Cover); Condition: Fair

Antonii Ballerini E Societate Iesu, Opus Theologicum Morale - Palmieri, Dominicus (Ex Officina Libraria Giachetti, Filii et SOC., 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Antonii Ballerini E Societate Iesu, Opus Theologicum Morale - Palmieri, Dominicus (Ex Officina Libraria Giachetti, Filii et SOC., 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Oeures Completes de Saint Francois de Sales - Sales, S. Francisco de (Libraire de Louis Vives, Editeur., 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Oeures Completes de Saint Francois de Sales - Sales, S. Francisco de (Libraire de Louis Vives, Editeur., 1892)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

ELEMENTOS DE PHILOSOPHIA - THIAGO SINIBALDI (TYPGRAPHIA DAS INSTITUICOES CHRISTAS, 1892)
Keywords: 16.Waterstains; 18.Bookworm; Condition: Fair; Hard Cover; Philosophy; Teaching